1998
DOI: 10.1073/pnas.95.21.12450
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of the closely related A and D genomes of the hexaploid oat Avena sativa L.

Abstract: A satellite DNA sequence, As120a, specific to the A-genome chromosomes in the hexaploid oat, Avena sativa L., was isolated by subcloning a fragment with internal tandem repeats from a plasmid, pAs120, that had been obtained from an Avena strigosa (As genome) genomic library. Southern and in situ hybridization showed that sequences with homology to sequences within pAs120 were dispersed throughout the genome of diploid (A and C genomes), tetraploid (AC genomes), and hexaploid (ACD genomes) Avena species. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
149
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(152 citation statements)
references
References 23 publications
3
149
0
Order By: Relevance
“…The similarity coefficients were consistently higher in the RFLP analysis (Nocelli et al,1999). Linares et al (1998) described molecular structure and chromosomal organization of the As120a repeated sequence isolated from the A. strigosa genome. The nucleotide sequence determination showed that the fragment was composed of a tandemly repeated DNA sequence adjacent to an unrelated sequence.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The similarity coefficients were consistently higher in the RFLP analysis (Nocelli et al,1999). Linares et al (1998) described molecular structure and chromosomal organization of the As120a repeated sequence isolated from the A. strigosa genome. The nucleotide sequence determination showed that the fragment was composed of a tandemly repeated DNA sequence adjacent to an unrelated sequence.…”
Section: Introductionmentioning
confidence: 77%
“…The D genome of the hexaploids is considered to have substantial similarities with the A genome based on GISH results (Chen and Armstrong, 1994;Jellen et al, 1994;Hayasaki et al, 2000). On the other hand, discrimination of the closely related A and D genomes is possible using an A genomespecific AS120a sequence (Linares et al, 1998). The AC1 (A. maroccana) and AC2 tetraploid (A. murphyi) are always grouped with the ACD hexaploids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A genome-specific repetitive family As120a isolated from the diploid species A. strigosa (As) consists of tandem arrays of 114-bp monomeric units (Linares et al, 1998). The As120a homologous sequences labeled only 14 chromosomes of the hexaploid A. sativa genome with a hybridization pattern similar to that of A. strigosa chromosomes.…”
Section: Satellite Dna Families In Hybrid Polyploidsmentioning
confidence: 99%
“…The satellite repeat thus allowed a distinction to be made between the otherwise closely related A and D genomes in the hexaploids. The lack of in situ hybridization of this satellite repeat to AACC tetraploids A. maroccana and A. murphyi suggests that a great genomic reorganization of As120a satellite sequences has occurred in the present day AACC tetraploids, probably by deletion events (Linares et al, 1998).…”
Section: Satellite Dna Families In Hybrid Polyploidsmentioning
confidence: 99%